Effects of Urease Inhibitor and Nitrification Inhibitor on the Nitrogen Losses, Physiological Activity, and Oil Palm Yield on Red-Yellow Podzolic - Melisa Melisa; Eka Tarwaca Susila Putra; Eko Hanudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Nitrogen (N) fertilizer efficiency can increase by adding N-(n-butyl) thiophosphoric triamide (NBPT) and N-(n-propyl) thiophosphoric triamide (NPPT) as urease inhibitor in urea fertilizer and adding 3,4-dimethyl pyrazole phosphate (DMPP) as nitrification inhibitor in ammonium sulfate (ZA) fertilizer. The research objectives were to examine the effectiveness of urease inhibitor (NBPT and NPPT) and nitrification inhibitor (DMPP) on the physiological activity and oil palm yield on red-yellow podzolic. Field experiment was done using a Randomized Complete Block Design (RCBD) of single factor and three replications as block. The single factor was nine fertilization treatments of urea with or without urease inhibitor, and ZA with or without nitrification inhibitor. The use of urease inhibitors decreases the amount of volatilization and N loss fertilizer. The higher dose of broadcasting N fertilizer (on the same type of fertilizer) resulted in the higher amount of N loss and volatilization. All fertilization treatments did not have any significant influence to the width and the length of opening stomata, nitrate reductase activity (NRA), N concentration in oil palm leaf, Oil Extraction Rate (OER), and Free Fatty Acid (FFA). Meanwhile, The oil palms at yellow red podzolic applied with urea 195 kg/ha combined with 0.12% of NBPT-NPPT resulting in higher fresh fruit bunch productivity.